Developing Cross-Cultural Awareness in Middle School Vocabulary Teaching: An Affordance Theory Perspective - Yuan, Wen (International Journal of Social Sciences and Public Administration, 2025)
As globalization deepens and international interactions expand, nurturing talents with cross-cultural competence has emerged as a shared objective among nations worldwide. As a widely spoken language, English serves as a vital connector facilitating global communication. With the increase of communication and interaction among people, there is a pressing need to enhance learners' understanding of diverse world cultures. The cultivation of cross-cultural awareness is a hot topic in English teaching today. Integrating intercultural education into English teaching not only aids language acquisition but also fosters effective intercultural communication skills and strengthens students' cultural identity. Vocabulary, as the building block of language learning, mirrors societal changes and embodies rich cultural meanings.  Learning vocabulary well is beneficial to students' English learning and the cultivation of cross-cultural awareness. English learning should focus on the environment. Affordance gives teachers a chance to treat the classroom as an ecological environment and to make use of various potential resources effectively. Therefore, this paper employs affordance theory to explore an ecological teaching framework for cultivating cross-cultural awareness in English instruction. Through detailed case analyses, it aims to identify practical strategies that empower teachers to design learning contexts where students can naturally develop cross-cultural competencies, ultimately providing actionable insights for enhancing intercultural education in language classrooms.